Effect of Russian Current in Motor Performance among Chronic Stroke Survivors: A Pilot Study - Joshin Joy; Hariharasudhan Ravichandran; Noble Vavachan; Adwaid Nambiar; Archana Shetty; Joseph Oliver Raj Alexander (Archives of Medicine and Health Sciences)
Background and Aim: Stroke is a leading cause of permanent disability in developing nations. Motor impairment in stroke contributes to limitations in activities of daily life, participation in community, and overall quality of life. Recovery following stroke is challenged by poor lower-limb muscle performance interfering with balance, gait, and functional tasks. Objective: The objective of this study was to investigate the effect of Russian current over the quadriceps muscle in 10-m walk performance and Brunnstrom stages of lower-extremity recovery in chronic stroke survivors. Materials and Methods: The Institutional Review Board approval was obtained for this pilot study, and a total of 36 chronic stroke survivors were recruited from the outpatient department of Alva’s College of Physiotherapy and Research Center, Moodubidire, Karnataka. Consent was obtained from the voluntary participants, and they were randomly assigned to one of the two groups; intervention and the control groups. Participants in the intervention group received Russian current over the quadriceps muscle in addition to the conventional rehabilitation, whereas the control group participants received only conventional rehabilitation. The study duration was 6 weeks. The outcomes measured were 10-m walk test and Brunnstrom stages of lower-extremity recovery. Results: Statistical analysis was performed with SPSS statistical software. The Kolmogorov–Smirnov test was performed for normality. The paired t-test, within-group analysis, demonstrated a significant increase in the 10-m walk test (P < 002) and Brunnstrom stage of lower extremity (P < 0.043) for the intervention group. The independent t-test demonstrated a highly significant (P = 0.001) value for the intervention group than the control group. Conclusion: Statistical results conclude that Russian current is effective in improving 10-m walk performance and Brunnstrom stages of motor recovery of lower limb in chronic stroke survivors.